The Creationists - Numbers, Ronald L. (Berkeley University of California Press, 1993)
Forty-seven percent of the American people, according to a 1991 Gallup poll, believe that God made man--as man is now--in a single act of creation, and within the last ten thousand years. Ronald L. Numbers chronicles the astonishing resurgence of this b
Keywords: Creationism